Genetic improvement of Kankrej cattle through associated herd progeny testing under field and farm conditions - SINGH, UMESH; RAJA, T V; ALYETHODI, R R; RATHOD, B S; PRAKASH, BIRHAM; BHASIN, VINEET (The Indian Journal of Animal Sciences, 2018)
The genetic improvement programme of Kankrej cattle under AICRP on Cattle is implemented in their home tract for their conservation and propagation. The involvement of farmer’s animal under the programme has helped to create awareness among the cattle breeders on the importance of this valuable breed. The production of frozen semen doses of genetically superior young bulls and providing the AI facility at the doorstep of the farmer has motivated and increased the conception rate to a large extent. The average age at first calving (AFC), first lactation 305 days milk yield, first lactation length and first peak yield were 1273.44±39.87 days (41.85 months), 2295.27±133.83 kg, 312.13±11.94 days and 10.53±0.51 kg, respectively. The average first service period and dry period were 149.81±16.27 and 126.30±13.31 days and overall lactation average dry period, service period and calving interval were 144.74±9.65, 169.39±15.03 and 434.24±12.94 days, respectively. The average all lactation 305 days milk yield, lactation length and days to attain peak yield were 2627.35±119.42 kg, 307.57±08.54 days and 55.75±6.12 days, respectively. The wet average and dry average were 8.58 and 5.38 kg, respectively. The performance of Kankrej cattle has improved over the years due to the implementation of the project and continuous efforts will be made to propagate this valuable germplasm to the needy people of the country.